Social psychology - Myers, David G. (Boston McGraw-Hill, 2008)
Adopting a multicultural approach, this text guides readers in the study of social thinking, social influence, and social relations. This edition emphasises social psychology's applications to both work and life, and uses vignettes to emphasise the relevance of social psychology research.
Includes bibliographical references (p. R-1-R-92) and indexes.
Keywords: Social psychology